Sports Injuries and the Right to Compensation - Sadler, Pauline; Guthrie, Rob (2001)
This article discusses issues relating to workers compensation and alternatives to compensation for sporting injuries. The rationale for the exclusion of sportspersons from most statutory compensation schemes is also evaluated. Section 11 of the Workers Compensation and Rehabilitation Act 1981 (WA) and the Sporting Injuries Insurance Act 1978 (NSW) are considered.